Eastern Caribbean Currency Union : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The objective of this paper is to analyze the growth performance of the ECCU countries since independence and the policy challenges they face to ensure sustained growth in the period ahead. Although tourism specialization may bring about higher growth, it could also increase volatility in growth by amplifying the impact of business cycles in source countries on the tourism sector. Low productivity growth is principally the reason for the slowdown in growth. High debt levels have been a major drag on growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet